Pendampingan Kegiatan Pelatihan Desain Grafis Untuk Warga Desa Ciputri Di Kecamatan Kaduhejo Kabupaten Pandeglang - Usep Saepul Mustakim (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2022)
Abstract Pondok Pesantren, is an educational institution that provides formal education to students aged children. There are many Islamic boarding schools scattered in various villages in Ciputri Village. The low design ability of santri and students is very unfortunate even though they are the successors to the next civilization. Besides that, in Ciputri village there is no course institution for graphic design training, so graphic design training is held within 1 day. The purpose of this activity is to increase the creativity of students and students in the world of design. Make students and students independent so that they can make designs such as pamphlets, banners or banners themselves and do not use the services of a printing company. This training is carried out by delivering material and direct practice for students and students. Participants can get to know graphic design and can practice the applications used to create the graphic design.